The Portrayal of Jesus in the Film Son of God - Samuel Anggi Suryonugroho (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
This thesis discusses how Jesus is portrayed as a New Messiah in the film Son of God. In the Son of God, Jesus is completely a different Messiah compared to the most popular concept about Messiah in the first century. Jewish people believed that a Messiah would come with similar characteristics like King David who was strong, gathering a strong army to beat the enemy and set the people free from oppression. By using the theory of Messiah, I would like to analyze how Jesus is portrayed as a new Messiah. Jesus came as a humble man in a poor family. During his ministry, he gathered low-profile disciples because his intention was not to build an earthly kingdom but the divine one. He served the people by performing miracles by his own authority to show that he had divine nature. Jesus also experienced suffering and death in order to save the people from eternal death. The last, Jesus resurrected from death proving that all of his Messianic claims were true and he had divine nature.Keywords: Messiah, the Davidic Messiah, Jesus